The Impact of Postpartum Posttraumatic Stress and Depression Symptoms on Couples’ Relationship Satisfaction: A Population-Based Prospective Study - Garthus-Niegel, Susan; Horsch, Antje; Handtke, Eric; von Soest, Tilmann; Ayers, Susan; Weidner, Kerstin; Eberhard-Gran, Malin (Frontiers in Psychology, 2018)
The couple relationship is of particular importance in the transition to parenthood and in the early childhood years because it is related to the well-being and mental health of partners, children, and the family. One factor that may substantially influence relationship quality and couple satisfaction after childbirth is the woman’s experience of birth. Approximately 2-4% of women develop posttraumatic stress disorder (PTSD) after childbirth, with potentially wide-ranging negative consequences for the women themselves and their families. To date, some qualitative studies have explored the influence of postpartum PTSD on couple relationship satisfaction. However, quantitative studies are sparse, with mixed results and methodological limitations. We hypothesized that postpartum PTSD will be prospectively associated with low couple relationship satisfaction, even when taking into account a variety of potential confounding variables, and that the effect of postpartum PTSD symptoms on couple relationship satisfaction will be mediated by postpartum depression symptoms. This study is based on data from the Akershus Birth Cohort study, a prospective cohort study. Information from hospital records and questionnaires completed at 17 weeks gestational age, as well as at 8 weeks and 2 years postpartum were used (n = 1480). PTSD symptoms were measured by the Impact of Event Scale and couple relationship satisfaction was assessed using a modified version of the Mehrabians Marital Satisfaction Scale. Depressive symptoms were assessed by the Edinburgh Postnatal Depression Scale. Data were analysed using bivariate correlations, multivariate regression analyses, and mediation analyses. Postpartum PTSD symptoms were prospectively related to low couple relationship satisfaction at two years postpartum, even when controlling for a considerable number of background factors. When including postpartum depression symptoms as predictor in the analyses, the effect of postpartum PTSD was no longer significant. Moreover, more detailed analyses showed that postpartum depression symptoms acted as a significant mediator, fully explaining the association of postpartum PTSD with couples’ relationship satisfaction. Early detection of couples’ relationship problems and the provision of professional help, particularly in high-risk couples may not only improve the quality of the couple relationship but also improve parenting and promote positive child outcomes.